Fiber Quality of Iranian Carpet-Wool Sheep Breeds - H R Ansari-Renani (Media Peternakan, 2012)
This experiment was aimed to identify characteristics and comparative merits of Iranian sheep wool breeds. Fiber characteristics of 75 male and 137 female of 1, 2, 3 and 4 yr of age belonging to Afshari, Zandi, Mehrabani, Lori, and Baluchi sheep breeds were studied. Samples of fiber were taken from the left midside of sheep and analyzed using standard objective measurements for staple length (SL), mean fiber diameter (MFD), coefficient of variation of fiber diameter (FDCV), inner coat fiber ICF, outer coat fiber (OCF), kemp fiber (KF) and yield (Y). A general linear model including sex and age as fixed effects and breed as random effect was used to analyze the data. The mean (and s.e) for SL, MFD, FDCV, ICF, OCF, KF and Y were 110.8±0.1 mm, 36.9±0.5 µm, 50.2%±0.8%, 84.2%±0.6%, 9.8%±0.4%, 5.9%±0.4% and 69.3%±0.7% respectively. MFD of 22% of all  wool samples was between 22-30 µm. MFD of a further 36% and 42% of wool samples was between 31-37  µm and coarser than 37 µm.  SL of 12% of wool samples was shorter than 100 mm and 38% of samples between 100-120 mm and 50% of samples were longer than 120 mm. There is substantial scope to improve the quality of fiber produced by Iranian sheep breeds through genetic selection.